Distinct profiles of immune cell populations underlie in-stent restenosis: a cluster analysis approach. (14th October 2021) - Rodriguez-Carrio, J; Bangueses, R; Rodriguez, I; Pevida, M; Llames, S; Meana, A; Lozano, I; Suarez, A
Abstract: Background: In-stent restenosis (ISR) is a major challenge in patients with coronary artery disease due to its association with poor clinical outcomes, quality of life and costs. ISR etiopathogenesis remains unclear, but traditional risk factors cannot fully explain ISR burden. Inflammation-driven loss of endothelial homeostasis and neoatherosclerosis are thought to hallmark ISR. Recently, a number of immune cell subsets have been related to vascular repair failure and endothelial damage, such as angiogenic T-cells (Tang), endothelial progenitor cells (EPC), senescent T-cells (CD4+CD28null), monocyte subsets and low-density granulocytes (LDG). However, these subsets have not been studied in ISR and an integrative analysis is lacking. Purpose: 1) to evaluate potential alterations in vascular repair and endothelial damage cellular mediators in ISR and 2) to identify profiles associated with clinical features. Methods: Case-control study including 30 patients with ≥1 previous stent implantation (15 bare metal stents (BMS) and 15 drug-eluting stents (DE)) which suffered restenosis and 30 patients with ≥1 BMS without restenosis, both confirmed in a second angiogram performed by clinical symptoms >8 months after index procedure. Cellular mediators of vascular homeostasis were quantified by flow cytometry based on their surface markers in peripheral blood (EPC: CD34+VEGFR2+CD133+; EC: CD34-VEGFR+CD133-; Tang: CD3+CD31+CXCR4+; senescent T-cells: CD4+CD28null) or in peripheral blood mononuclear cells (monocyte subsets, ACE expression; total LDG: CD15+; and LDG subsets: CD15+CD14-CD16- and CD15+CD14lowCD16+). Results: Patients with ISR exhibited decreased circulating Tang (p=0.005) and EPC (p<0.001), whereas CD4+CD28null and EC counts were higher (p<0.0001 and p=0.006) compared to ISR-free patients. No differences were observed in the frequency of monocyte subsets (all p>0.050), although ACE expression was found to be increased (non-classical p<0.001; and intermediate p<0.0001) in ISR. Moreover, no differences were noted in the total LDG population (p=0.092), but an increase in the CD14- compartment was observed in ISR (p=0.004). An unsupervised cluster analysis built with these subsets informed the presence of three profiles (Figure 1): group I (hallmarked by a profound impairment in vascular repair and augmented damage, suggestive of central haematopoiesis traits) exhibited an enhanced clinical risk profile compared to group II (hallmarked by a mid-altered vascular repair) and group III (hallmarked by CD16+ shifted LDG and ACE expression) (Figure 2). No differences were observed in stent types or traditional risk factors but hypertension. Conclusions: Profound alterations in immune populations related to vascular repair and endothelial damage are found in ISR. Distinct cellular profiles can be distinguished within ISR, suggesting that different alterations may uncover different ISR clinical phenotypes, in terms of severity and extension. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): ISCIIIPrograma Intramural ISPA